The development of MUET Corpus and MUETapp - Khamis, Noorli; Basiron, Halizah; Lee, Mei Ph'ng; Osman, Mashanum; Naim@ Mohayat, Mohd Hariz; Abdul Rahim, Razilah; Abdul Bareed, Nurhidayah (UTeM, 2020)
With the emergence of Industry 4.0, this study takes into consideration the application of the digitalisation era in education. The prevalent use of mobile devices, such as mobile phones, has an impact on how students learn, especially in the case of foreign language learning. Despite the fact that a large vocabulary is a powerful unit in language learning, it poses challenges to the MUET candidates in scoring good bands. Thus, this project intends to focus on expanding the vocabulary knowledge of the MUET candidates by capitalising on the technology in education. The project looks at the development of the MUET Corpus and MUETLex (a mobile language learning application). A collection of MUET question papers has been obtained from the Malaysian Examination Council (MPM). Next, the corpus of the question papers (the MUET corpus) will be developed and analysed to determine the vocabulary profile of the MUET question papers. Several other types of linguistic analyses will be carried out to further define the vocabulary in contexts. Next, the study will involve identifying the equivalent Malay language (Bahasa Melayu) translation of the vocabulary from the Malay Language Dictionary (Kamus Bahasa Melayu), Dewan Bahasa & Pustaka (DBP), before devising the list of bilingual dictionary entries of MUET question papers. This list has been used in the development of MUETLex – the first MUET mobile application in Malaysia. The MUET corpus will serve as the database for other aspects of investigation of the MUET question papers in the future. The list will be used for the development of a mobile language learning application - a bilingual (English-Bahasa Melayu) MUET dictionary (the MUETApps). This attempt is hoped to contribute significantly in improving the MUET candidates’ vocabulary knowledge, thus preparing them better for MUET.